Effect of co-digestion of tylosin fermentation dreg and food waste on anaerobic digestion performance. (April 2021) - Gao, Ming; Yang, Min; Ma, Xinxin; Xie, Dong; Wu, Chuanfu; Wang, Qunhui
Graphical abstract: Highlights: This study investigated the co-digestion of TFD and food waste. pH, TVFA and acetic acid were the most important factors affecting CH4 production. Tylosin concentration decreased significantly after anaerobic digestion. This study provided a feasible method for the treatment of TFD. Abstract: In this study, the effects of adding different food waste proportions (volatile solids ratio of 3:7, 5:5, 7:3) to tylosin fermentation dreg on anaerobic digestion were investigated. The results showed that the co-digestion group (294–399 mL·g-VS −1 ) increased methane production by 14.8%–55.5% compared with tylosin fermentation dreg alone-digestion (256 mL·g-VS −1 ). The correlation analysis showed that pH, total volatile fatty acids and acetic acid were the most important factors affecting cumulative methane production. Tylosin in the solid and liquid phases decreased significantly after anaerobic digestion, indicating that tylosin could be effectively removed by co-digestion, and the total removal rate was 68.2%–83.7%. Therefore, due to the satisfactory methane yield and the tolerable tylosin removal rate, it is feasible to make the co-digestion of tylosin fermentation dreg and food waste.